International Capital Markets : Recent Develpments and Short-Term Prospects, 1981. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1981)
This paper provides a review of recent developments and an assessment of short-term prospects for private international capital markets, which constitute one of the main sources of international capital flows.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet